A Staged Biventricular Approach Combining the Starnes and Cone Procedures in Ebstein’s Anomaly: A Case Report and Literature Review - Paul Linnenbank; Daniel Biermann; Eike Philipp Schneider; Ida Hüners; Nora Lang; Fridrike Stute; Thomas S. Mir; Michael Hübler; Rainer Kozlik-Feldmann; Jakob Olfe (Children)
Background: Severe neonatal Ebstein’s anomaly (EA) is associated with a high risk of mortality. A new therapeutic approach aims to combine the advantages of Starnes’ procedure in stabilizing critically ill neonates with the long-term superiority of biventricular physiology after cone reconstruction. Case report: The echocardiography of a male preterm (36 weeks’ gestation; birth weight 2400 g) demonstrated EA Carpentier type C, membranous pulmonary atresia, and hypoplastic pulmonary arteries (PAs). After undergoing the Starnes procedure postnatally, multiple dilatations of the AP shunt and the Starnes fenestration followed. Cone reconstruction was performed at 15 months of age. Surgical revision addressed tricuspid and pulmonary valve insufficiency and PA bifurcation stenosis. Subsequently, PA branch stenosis with severe impairment of right ventricular function and dilatation required stent implantation. At the last follow-up, at 3 years of age, the patient was asymptomatic with sufficient exercise tolerance. Discussion: The American Association for Thoracic Surgery recently recommended evaluating all Starnes patients for potential conversion to cone. Consequently, the Starnes procedure should be modified to facilitate subsequent biventricular correction. Both the optimal timing of conversion and the appropriate assessment to reliably evaluate feasibility and the prospects for success require further investigation. Conclusions: Conversion from Starnes to cone is technically feasible, even in cases of severe EA, prematurity, low birth weight, and additional cardiac comorbidities, and provides promising initial results. Further research is needed to define candidacy and the optimal timing of conversion, and to assess long-term outcomes. The high therapeutic effort and complexity make this treatment approach suitable only for quaternary centers.